Impact assessment of cluster approach in integrated coconut management - Swapna Surendran (Department of Agricultural Economics, College of Horticulture, 2008)
Cluster approach in integrated coconut management is a programme implemented by the Coconut Development Board in which a contiguous area extending up to 25 hectares is registered as a cluster. Landholdings ranging from five cents to four acres, accommodating one to 200 palms are included in the cluster and the scheme envisages a financial assistance up to Rs 7000 per acre for two consecutive years. The programme was implemented on a pilot basis in the year 2005-06 in four clusters of Alappuzha district viz. Kanjikuzhy, Pattanakkadu, Uzhuva and Muthukulam. The study was intended to assess the trend in area, production and productivity of coconut in Kerala as well as Alappuzha district and to assess the changes in coconut crop status and income status of farmer groups.